2013
DOI: 10.3347/kjp.2013.51.1.75
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiological Study of Cutaneous Leishmaniasis in Al-Jabal Al-Gharbi, Libya

Abstract: Cutaneous leishmaniasis (CL) is an endemic parasitic infection in the Mediterranean region, including Libya and its Al-jabal Al-gharbi province. We aimed at studying the occupational relevance as well as other epidemiological aspects of CL. We investigated 140 CL cases who attended at Gharyan outpatient polyclinic during a period of 6 months in 2009. CL infection was clinically diagnosed and confirmed by demonstration of Leishmania parasites on smears from lesions. Our findings showed that males were more affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
9
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 11 publications
13
9
3
1
Order By: Relevance
“…20 Other studies indicate sizes of CL lesions to range between 5 and 200 mm. 11 However, our analysis of lesion numbers between Syrian and Turkish patients in this study revealed significantly greater numbers of CL lesions in Syrian patients. The number of lesions in Turkish CL patients was determined as 1.93 ± 1.47, whereas in the Syrian patient group, the mean number was determined as 2.46 ± 2.43.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…20 Other studies indicate sizes of CL lesions to range between 5 and 200 mm. 11 However, our analysis of lesion numbers between Syrian and Turkish patients in this study revealed significantly greater numbers of CL lesions in Syrian patients. The number of lesions in Turkish CL patients was determined as 1.93 ± 1.47, whereas in the Syrian patient group, the mean number was determined as 2.46 ± 2.43.…”
Section: Discussioncontrasting
confidence: 57%
“…11 In conclusion, we demonstrated variations in the clinicoepidemiological features of CL between Turkish and Syrian patients within the Sanliurfa province. Specifically, we showed that the disease duration is significantly higher for Turkish patients, whereas the number of lesions is greater in the Syrian patient group.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…In a study in Libya 16 , it was found that being engaged in farm activities was a risk factor, increasing the exposure to ACL infection, as was an occupational requirement to stay outdoors during part of the night.…”
Section: Discussionmentioning
confidence: 99%